Investigation of Heavy Metal Contamination in Bread Baked and Sold in Makurdi Metropolis, Benue State Nigeria - Joseph, Ikwebe; David, Bando Christopher (Darul Yasin Al Sys, 2024)
Heavy metals are pollutants that are of global significance due to their toxicological properties when their intake significantly exceeds recommended levels. They are persistent in the environment, and may be unintentionally present in raw materials used for production of bread; they may migrate from packaging into food, or find their way into finished food products due to anthropogenic activities. The present study investigated the presence of heavy metals in bread baked and sold in Makurdi, Metropolis, to ascertain their safety for consumption. Twenty different bread brands were sampled twice from bakeries and distribution outlets within Makurdi, metropolis respectively. The heavy metal analysis was carried out using Atomic Absorption Spectrophotometer (AAS). The varied concentrations of heavy metals in mg/kg of Fe, Pb, Cr, Zn, Ni, and Cd in Bread Loaves from Bakeries (BFB) and in Bread Loaves from Distribution Outlets (BFD) were determined. Cd was not detected in BFB and flour, but it was present in one sample in BFD. Duncan Multiple Range Test (DMRT) was employed to separate the means. Though, most of the studied heavy metals were within permissible limits, caution should be taken when consuming bread, because of their ability to persist and bio-accumulate in bio-systems.